2008
DOI: 10.1002/jmv.21154
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mixed infection cases with both herpes simplex virus types 1 and 2

Abstract: Herpes simplex virus type 1 (HSV-1) is isolated principally from the upper half of the body innervated by the trigeminal ganglia whereas herpes simplex virus type 2 (HSV-2) is generally isolated from the lower half of the body innervated by the sacral ganglia. However, recent reports suggest that HSV-1 and HSV-2 can each infect both the upper and lower half of the body causing a variety of symptoms and there is a possibility that HSV-1 and HSV-2 infections can occur simultaneously with both causing symptoms. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…HSV-2 rarely causes keratitis, and the copy number of HSV-2 DNA in viruses isolated from patients with herpetic keratitis because of a mixed infection with HSV-1 and HSV-2 was approximately 1% of that of HSV-1. 2 These observations indicate that HSV-2 does not have any preference for the cornea as a host tissue, which is reflected in the fact that HSV-2 DNA was detected in only 1 patient in this study. Taken together, these results indicate that frequencies of the 4 herpesviruses in the cornea depend on the frequency of corneal disease associated with each herpesvirus, as suggested in past reports.…”
Section: Discussionmentioning
confidence: 73%
“…HSV-2 rarely causes keratitis, and the copy number of HSV-2 DNA in viruses isolated from patients with herpetic keratitis because of a mixed infection with HSV-1 and HSV-2 was approximately 1% of that of HSV-1. 2 These observations indicate that HSV-2 does not have any preference for the cornea as a host tissue, which is reflected in the fact that HSV-2 DNA was detected in only 1 patient in this study. Taken together, these results indicate that frequencies of the 4 herpesviruses in the cornea depend on the frequency of corneal disease associated with each herpesvirus, as suggested in past reports.…”
Section: Discussionmentioning
confidence: 73%
“…The contralateral eye is infrequently affected either simultaneously or subsequently (Liesegang 2001), although people with atopy or an immune deviation may be predisposed to HSV epithelial keratitis of both eyes (Souza 2003; Wilhelmus 1981c). Besides HSV-1, much less common causes of dendritic epithelial keratitis are HSV-2 (Kaneko 2008; Neumann-Haefelin 1978; Vannini 1986), varicella-zoster virus (Bierly 1994; Hu 2010; Pavan-Langston 1973), co-infection with HSV-1 and human herpes virus 6 (Okuno 2011) and, very rarely, cytomegalovirus (Wilhelmus 1996b), Epstein-Barr virus (Pflugfelder 1990), or adenovirus (Chodosh 1995). Laboratory testing can help to establish the etiology of atypical cases (Chanzy 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas it was previously suggested that oral and genital infections were primarily associated with HSV-1 and HSV-2, respectively, an increase in the incidence of genital HSV-1 infection has been seen over the past 20 years (4,9,16,18,29). As a result of the clinical significance of the pathogens in terms of prevalence and morbidity, a number of investigative teams have developed vaccines to HSV-1 or HSV-2, some of which have been evaluated against HSV-1 and/or HSV-2 (2,5,11,15,20,22,26,32,33,41).…”
mentioning
confidence: 98%